2018
DOI: 10.1097/dss.0000000000001394
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Assessment of Postoperative Bleeding Complications in Anticoagulated Patients Following Mohs Micrographic Surgery

Abstract: Dermatologic surgeons should manage both traditional oral anticoagulants and novel oral anticoagulants in a similar manner. Future studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 24 publications
1
35
0
3
Order By: Relevance
“…It has been previously shown that there is an up to 6.7% risk of SSI occurrence after microscopically controlled surgery, regardless of the immune status of the patient [7]. The incidence of bleeding as a complication in dermatological surgery is reported to be between 1.4 % and 7.14 % [10--12]; however, in these investigations microscopically controlled surgery was not analyzed separately from other types of procedures. Due to the limited evidence on the complication rates for microscopically controlled surgery (next‐day surgery) performed in an inpatient setting in Germany, there is currently no national guideline on the use of perioperative antibiotic prophylaxis (PAP) in dermatosurgery.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that there is an up to 6.7% risk of SSI occurrence after microscopically controlled surgery, regardless of the immune status of the patient [7]. The incidence of bleeding as a complication in dermatological surgery is reported to be between 1.4 % and 7.14 % [10--12]; however, in these investigations microscopically controlled surgery was not analyzed separately from other types of procedures. Due to the limited evidence on the complication rates for microscopically controlled surgery (next‐day surgery) performed in an inpatient setting in Germany, there is currently no national guideline on the use of perioperative antibiotic prophylaxis (PAP) in dermatosurgery.…”
Section: Introductionmentioning
confidence: 99%
“…The combined evidence from six studies derived predominantly from hospital-based settings revealed no difference in the rate of occurrence of perioperative bleeding or hematoma in patients who had been administered a relevant pharmacologic agent prior to the onset of surgery, as versus those who had not. [22][23][24][25][26][27] Most selected studies compared aspirin, warfarin, or clopidogrel to placebo or no medication, [22][23][24]26 and one also assessed the effect of newer anticoagulant agents. 27 Studies were generally of low quality, with the reported duration of bleeding assessment after surgery ranging from immediately after completion of surgery to 4 weeks later.…”
Section: Optionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Most selected studies compared aspirin, warfarin, or clopidogrel to placebo or no medication, [22][23][24]26 and one also assessed the effect of newer anticoagulant agents. 27 Studies were generally of low quality, with the reported duration of bleeding assessment after surgery ranging from immediately after completion of surgery to 4 weeks later. [24][25][26][27] All but one of the selected studies assessed the bleeding risk on both flap and graft repairs, [22][23][24][25]27 with one including flaps only.…”
Section: Optionmentioning
confidence: 99%
“…In a survey of 174 ACMS members, bleeding was the most frequently reported adverse event 20 . Flaps, grafts, and larger postoperative defect sizes have been described as significant predictors for hemorrhagic complications 21 . To avoid hemorrhagic complications, it is essential to review each patient's medication and supplement list before surgery.…”
Section: Hemorrhagementioning
confidence: 99%
“…For warfarin, it is considered safe to operate if the INR is between 2 and 3.5 28 . Investigations of the novel oral anticoagulant agents (NOACs) including dabigatran, apixaban, and rivaroxaban have also demonstrated low hemorrhagic complication rates similar to those of traditional oral agents, and no severe or life‐threatening hemorrhagic complications 21,29,30 . At the current time, guidelines suggest continuing NOAC agents for dermatologic surgery 31,32 .…”
Section: Hemorrhagementioning
confidence: 99%